2002
DOI: 10.1042/cs103041p
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden Polymorphism and the Rate of Fibrosis Development in Chronic Hepatitis C Virus Infection

Abstract: Background: The rate of progression to cirrhosis varies among individuals chronically infected with the hepatitis C virus (HCV). Coagulation pathway activation in models of hepatic fibrosis suggests variation in coagulation pathway components may influence the rate of fibrosis. We hypothesised that polymorphisms of the coagulation factors II and V affect the rate of progression to cirrhosis in HCV infected subjects. Methods: We studied the relationship between rate of fibrosis (calculated by dividing the fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
2
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 11 publications
6
83
2
5
Order By: Relevance
“…Nonetheless, evidence for the role of thrombosis in liver fibrogenesis has been increasing in recent years. While possession of Factor V Leiden mutations has been shown to be a risk factor in rapid fibrosis progression in HCV [61], low-molecular weight heparin and warfarin prevented hepatic fibrogenesis caused by carbon tetrachloride in the rat [62]. Furthermore, the influence of Factor V Leiden polymorphism on fibrosis progression has been confirmed experimentally [63].…”
Section: Role Of Hepatic Sinusoids In the Pathogenesis Of Congestive mentioning
confidence: 61%
“…Nonetheless, evidence for the role of thrombosis in liver fibrogenesis has been increasing in recent years. While possession of Factor V Leiden mutations has been shown to be a risk factor in rapid fibrosis progression in HCV [61], low-molecular weight heparin and warfarin prevented hepatic fibrogenesis caused by carbon tetrachloride in the rat [62]. Furthermore, the influence of Factor V Leiden polymorphism on fibrosis progression has been confirmed experimentally [63].…”
Section: Role Of Hepatic Sinusoids In the Pathogenesis Of Congestive mentioning
confidence: 61%
“…Firstly, as described above, epidemiological studies have demonstrated an association between thrombophilic conditions and more advanced hepatic fibrosis (Wright et al, 2003;Papatheodoridis et al, 2003;Poujol-Robert et al, 2004;Plompen et al;. Secondly, in addition to its role in activating fibrinogen, thrombin has been shown to promote fibrogenesis via protease-activated receptor (PAR)-mediated activation of hepatic stellate cells (HSC) (Anstee et al, 2011).…”
Section: How Safe Is Anticoagulation Therapy To Use In Those With Chrmentioning
confidence: 99%
“…Papatheodoridis and colleagues demonstrated that patients with either chronic hepatitis B or hepatitis C virus infection with advanced fibrosis (Ishak stage 4-6) were significantly more likely to have thrombophilia related to deficiencies of protein C, plasminogen and anti-thrombin III compared to patients with milder fibrosis (Papatheodoridis et al, 2003). Furthermore, Factor V Leiden (FVL) -a well-characterised mutation in the coagulation system, which causes activated protein C resistance and amplification of the coagulation cascade -conferred a near fourfold increase in the risk of rapidly-progressive fibrosis in a Caucasian population with chronic hepatitis C virus (HCV) infection (Wright et al, 2003). Protein C deficiency, increased expression of factor VIII and hyperhomocysteinemia have also been associated with accelerated fibrosis in patients with chronic HCV (Poujol-Robert et al, 2004), whilst a Dutch population-based cohort study identified presence of FVL or prothrombin G202010A mutations as independent risk factors for a liver stiffness score of ≥ 8.0kPa on transient elastrography (Plompen et al, 2015).…”
Section: How Safe Is Anticoagulation Therapy To Use In Those With Chrmentioning
confidence: 99%
“…The role of the clotting cascade has received much attention in studies of pulmonary fibrosis (72), and recent studies in liver fibrosis have implied a role, particularly for thrombin, in promoting the fibrotic response. Indeed, the procoagulant state associated with factor V Leiden is also associated with the progression of fibrosis in chronic HCV infection (73).…”
Section: Regulation Of Hsc Phenotype In Liver Injurymentioning
confidence: 99%